2018
DOI: 10.17523/bia.2018.v75.e1412
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação de intervalos de tempo para registro do comportamento ingestivo de bovinos confinados individualmente

Abstract: RESUMO: O objetivo desse trabalho foi comparar o intervalo de tempo de registro de cinco minutos com quatro intervalos de tempo (10, 15, 20 e 30 minutos), para avaliação dos comportamentos comendo, ruminando, em ócio, em pé, apresentados por bovinos confinados individualmente. Foram utilizados 62 machos Nelore desmamados, confinados durante 112 dias. O comportamento foi registrado a cada 28 dias, durante 24h, por observações diretas com rota de amostragem scan e intervalos de registro de 5 minutos, para o cálc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…In the present study, the number of periods was not considered. However, it is important to note that the observation interval adopted when evaluating the ingestive behavior of herbivores should be considered with caution if the aim is evaluating periods and time per period since studies with sheep (Fischer et al, 2000;Carvalho et al, 2007;Marques et al, 2012) and cattle (R. R. Silva et al, 2005;Aldrighi et al, 2018) showed that intervals greater than 5 minutes underestimate the quantification of periods and time by period. The choice of observation interval affects the perception of the observer concerning the heterogeneity of a system, and the use of an inappropriate scale can compromise the interpretation of results (Dutilleul, 1997).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, the number of periods was not considered. However, it is important to note that the observation interval adopted when evaluating the ingestive behavior of herbivores should be considered with caution if the aim is evaluating periods and time per period since studies with sheep (Fischer et al, 2000;Carvalho et al, 2007;Marques et al, 2012) and cattle (R. R. Silva et al, 2005;Aldrighi et al, 2018) showed that intervals greater than 5 minutes underestimate the quantification of periods and time by period. The choice of observation interval affects the perception of the observer concerning the heterogeneity of a system, and the use of an inappropriate scale can compromise the interpretation of results (Dutilleul, 1997).…”
Section: Resultsmentioning
confidence: 99%
“…The choice of the appropriate time interval for recording activities in the evaluation of ingestive behavior has been widely discussed since it allows the observation of the largest number of animals and does not compromise the accuracy of measuring the time spent in behavioral activities (Aldrighi et al, 2018). Considering that the diet used (Mazza et al, 2020;Herzog et al, 2021;Valença et al, 2022) and the production system (Poli et al, 2009) in which the animals are inserted can modify the ingestive behavior of sheep, it is suggested that these factors may change the observation interval to be adopted.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ingestive behavior was assessed individually every 10 minutes (Aldrighi et al, 2018) for 12 hours, starting at 7 am. The evaluations were carried out on the first day of each experimental period to avoid changes in the behavior of the animals caused by other collection management.…”
Section: Ingestive Behaviormentioning
confidence: 99%